2016
DOI: 10.1016/j.phrs.2015.12.023
|View full text |Cite
|
Sign up to set email alerts
|

Chronic mild stress-induced alterations of clock gene expression in rat prefrontal cortex: modulatory effects of prolonged lurasidone treatment

Abstract: Disruptions of biological rhythms are known to be associated with depressive disorders, suggesting that abnormalities in the molecular clock may contribute to the development of these disorders. These mechanisms have been extensively characterized in the suprachiasmatic nucleus, but little is know about the role exerted by individual clock genes in brain structures that are important for depressive disorders. Using the chronic mild stress model we found a significant reduction of BMAL1 and CLOCK protein levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 37 publications
5
26
0
Order By: Relevance
“…Both stressed and control groups were further divided into two subgroups, and for subsequent five weeks, they received the administration of vehicle (1% hydroxyethylcellulose, oral gavage) or lurasidone (3 mg/kg, oral gavage; Sumitomo Dainippon Pharma Co. Ltd, Japan) once a day. The dose of lurasidone was chosen on the basis of our previous work that showed its effectiveness in normalising the behavioural and the molecular alterations due to CMS exposure (Calabrese et al, 2016; Luoni et al, 2015; Rossetti et al, 2018). The volume of all injections was 1 mL/kg.…”
Section: Methodsmentioning
confidence: 99%
“…Both stressed and control groups were further divided into two subgroups, and for subsequent five weeks, they received the administration of vehicle (1% hydroxyethylcellulose, oral gavage) or lurasidone (3 mg/kg, oral gavage; Sumitomo Dainippon Pharma Co. Ltd, Japan) once a day. The dose of lurasidone was chosen on the basis of our previous work that showed its effectiveness in normalising the behavioural and the molecular alterations due to CMS exposure (Calabrese et al, 2016; Luoni et al, 2015; Rossetti et al, 2018). The volume of all injections was 1 mL/kg.…”
Section: Methodsmentioning
confidence: 99%
“…We have previously shown that CMS is able to induce depressive-like behaviors such as anhedonia (Rossetti et al, 2016) as well as cognitive impairment (Calabrese et al, 2017), which are associated with alterations in key molecular players for psychiatric disorders (Luoni et al, 2014; Calabrese et al, 2016b; Molteni et al, 2016). We also investigated the effect of a chronic treatment with lurasidone in counteracting the CMS-induced alterations in rat hippocampus.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the clock genes ( Arntl, Per2-3 ) of animals suffering from chronic mild stress (CMS) were strongly expressed in the PFC, but did not follow a circadian rhythm. The other study also found a reduction of the BMAL1 protein ( Arntl ) in the PFC of CMS rats (Calabrese et al, 2016; Christiansen et al, 2016). Consistent with our conclusions, one previous study reported EA can ameliorate the bowel dysfunction in spinal cord injury rats, and increase Per2 expression (Cheng et al, 2016).…”
Section: Discussionmentioning
confidence: 71%